IMPLEMENTASI DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT AEROFOOD INDONESIA (RS MAYAPADA HOSPITAL JAKARTA SELATAN) - Riski Meiliasari; Tarwijo (Journal of Research and Publication Innovation, 2024)
The importance of competitive advantage in business in today's global era is due to rapid economic growth and the need for high industrial expertise. Human resource management is a key element in achieving company goals, because quality human resources accelerate the achievement of goals. Discipline is also an important attitude in a company to maintain compliance with applicable guidelines. Quality human resources are very important for management effectiveness, so attention needs to be given to HR-related issues to maintain business continuity. Work discipline is important in manager and employee communication to increase individual awareness in complying with company regulations. Employee performance must focus on quality and quantity to achieve organizational goals. Employee performance assessments when serving customers are based on the level of discipline. Lack of discipline can hinder service and indicate suboptimal performance in tasks. Indicators of work discipline include attendance, compliance with regulations and work standards, level of alertness, and work ethics. This involves employee discipline in carrying out tasks responsibly.